ASSESSMENT OF SPATIOTEMPORAL VARIATION IN INTER-STATE PASSENGER FLOW FROM KATSINA, KATSINA STATE, NIGERIA - Yahaya, Olanrewaju Yusuf; Shafii, Husaini; Ubogu, Andrew Egba (Faculty of Social and Political Sciences University of Bangka Belitung, 2025)
This paper examines the nature, pattern, and spatiotemporal variation of inter-state passenger movement from Katsina to other states across the country. Two major terminals were purposefully selected for the study, which are the Nigerian Union of Road Transport Workers (NURTW) and Katsina State Transport Authority (KTSTA). Questionnaires were systemically administered to departing passengers. Information on passenger flow was collected from the passenger register at the motor parks. A flow line map was used to show the direction of the flow, while a bar graph was used to show the volume or magnitude and temporal variation of passenger movement from Katsina to other states across the country. The findings reveal that the majority of the passengers were males who were married, and most of them were traders and civil servants; thus, work- or business-related trips account for most of the reasons for travelling. The findings reveal that the NURTW terminal has a wider spatial coverage of 11 states, while the KTSTA terminal has a spatial coverage of 9 states. Kano State is the most popular destination, followed by Kaduna and Abuja. Generally, the findings show a seasonal pattern of passenger flow with higher numbers in the later months of the year (October to December) and lower numbers in the middle of the year (June and July). Recommendations include the enhancement of transport infrastructures to cater to work- or business-related trips, seasonal adjustment, passenger demographic consideration, and promotion of off-peak travel. This is to ensure a more efficient and responsive transport system that meets the needs of travellers and maximises customer satisfaction.